Variation in core clerkship grading reported on the Medical Student Performance Evaluation (MSPE) for orthopaedic surgery applicants: a retrospective review. Issue 5 (25th September 2022) - Vaghani, Parth; Samade, Richard; Gordon, Adam M.; Scharschmidt, Thomas J.; Goyal, Kanu S.
Abstract : Background: Heterogeneity of grading schema among medical schools complicates utility of core clerkship grades reported. The purpose of this study was to understand the variation in number and verbiage in grading schemes during third-year core clerkships for orthopaedic surgery residency applicants. Methods: Applications to a single institution's orthopaedic surgery residency program during the 2017-2018 match cycle were reviewed. Data extracted from the Medical Student Performance Evaluation (MSPE) included medical school name, number of core clerkships, grade options/tiers, and % grade distribution in clerkships. Applicant data collected included Step 1 Score, Step 2 Clinical Knowledge (CK) Score, Alpha Omega Alpha (AOA) membership status, clerkship grades, and medical school rank. Results: A total of 858 applications from 211 medical schools were reviewed. Further analysis was performed on 142 schools, representing 721 students, that reported grading distributions. The number of grade tiers varied from two to 11, with three (26.1%), four (43.7%), and five (20.4%) tiered grading systems being the most common. One-hundred unique verbiages were identified to describe grading among all schools. Schools ranked in the top 25 distributed honors more often than schools ranked outside the top 25 ( P <0.001). The median for the average percentage of honors distributed by a school was 32.3%, with a total range of 2.4% to 72.6%. A significant relationship between applicant match success and medical school grading practices could not be determined ( P =0.054). Conclusions: Significant differences in assigned grades by medical schools for third-year core clerkships were found. Therefore, students' core clerkship grades should be reviewed in the context of the grade distributions at their medical schools. Level of Evidence: Level IV.